Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hao, Hongjian; Wang, Rong; Li, Shicai; Pian, Duo; Peng, Ning; Sailike, Ahejiang; Yu, Zhouchang; Shi, Jiayi; Wang, Xingbo; Wang, Zihan; Zhang, Wei (Plant and soil, 2025)
Aims Plant and microbial residues are the primary drivers mediating soil organic carbon (SOC) accumulation in terrestrial ecosystems. However, how plant residues and microbial residues affect SOC accumulation and the underlying mechanisms remain poorly understood, especially in the succession process of different vegetation types. Methods In this study, grasslands (GL) and Robinia pseudoacacia plantations (RP) restored for 10, 20, 30, and 40 years were used as research subjects on the Loess Plateau, and farmland was used as a control. Several indicators of soil physicochemical and plant characteristics, enzyme activity, amino sugar, lignin phenols were measured. Results The results indicated that the contents of microbial and plant residue carbon in GL and RP increased with the increasing restoration years. However, the contribution of plant residue carbon to the SOC in GL and RP gradually decreased, while microbial residue carbon showed the opposite trend. In contrast, microbial residues were the main contributor to SOC in GL (62.8–75.1%), while plant residues were the main contributor to SOC in RP (47.2–58.3%). There was a difference in the bacterial and fungal residue carbon contribution to SOC between GL and RP. In GL, the dominant contributor to SOC changed from bacterial (47.7–37.2%) to fungal residues (15.1–37.9%). But in RP, it has always been dominated by fungal residue carbon (17.4–33.3%). Conclusions More SOC accumulated in GL and RP in the form of microbial and plant residue carbon, respectively. In GL and RP, the contribution of carbon from fungal residues increased with the increase of recovery years. Overall, our research not only contributes to understanding the complexity of the carbon cycle in ecosystems, but also provides a valuable scientific basis for the management of soil carbon pools in different vegetation types under climate change.